2020
DOI: 10.1177/1368430220929402
|View full text |Cite
|
Sign up to set email alerts
|

Detecting changes between two strangers: Insight from a classic change blindness paradigm

Abstract: The current study aims to investigate what factors influence whether adults detect a change between social partners in a brief interaction. In two experiments, we examined whether locale diversity, a stranger’s marginalized minority status (e.g., minority race, minority religious affiliation), and race congruence (e.g., own or other race) influenced the likelihood of being differentiated. Using a change blindness paradigm, an experimenter approached pedestrians asking for directions, then surreptitiously chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 38 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…By placing individuals in common situations (i.e., a virtual meeting where they complete online questionnaires), we are able to witness what individuals prioritize and dismiss in virtual situations. Building on prior research (Hirose & Hancock, 2007; Marquis et al, 2021), our results have implications for both social and cognitive psychology, suggesting that in-group and out-group biases can have an effect on change blindness rates. Virtual interactions are here to stay, and understanding how one’s attention may vary across virtual and real environments is of great importance.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…By placing individuals in common situations (i.e., a virtual meeting where they complete online questionnaires), we are able to witness what individuals prioritize and dismiss in virtual situations. Building on prior research (Hirose & Hancock, 2007; Marquis et al, 2021), our results have implications for both social and cognitive psychology, suggesting that in-group and out-group biases can have an effect on change blindness rates. Virtual interactions are here to stay, and understanding how one’s attention may vary across virtual and real environments is of great importance.…”
Section: Discussionsupporting
confidence: 56%
“…In E1, the RAs were both of African ethnicity and none of the participant ethnicities were African, while in E2, the RAs were both of European ethnicity, and 17 participants were also of European ethnicity, which could lead to enhanced memory for faces in E2. Additionally, prior research has found that Europeans show lower rates of change blindness (Marquis et al, 2021) and are better able to recall faces without a hijab than those with one (Megreya et al, 2012), which is known as the headscarf effect; because the RAs in E1 wore a headscarf while those in E2 did not, the headscarf effect may provide some explanation for the opposite change blindness rates across the two experiments. We would be remiss if we did not acknowledge the familial similarity between the E1 RAs, as they are presumably more facially similar than the RAs in E2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation